Assessment criteria in a holistic scoring scale as a pedagogical tool in teaching english language argumentative essay writing in a Malaysian secondary school - Kho, Sui Ju (2006)
This small scale study is spurred by two contrasting scenarios. On one hand, is the inundating emphasis on academic excellence in recent years that is highly prized by all parties concerned in the education fields including the students themselves. On the other hand, there are moans and groans on the declining standard of English language among Malaysian students despite the fact that communicative element is constituted as one of the important components in our current approach in the teaching and learning of English language. As a result, there is a tendency for the Malaysian classrooms to gear towards examination-oriented teaching and learning. In other words, backwash effects become dominant. This study explores the possibility of using assessment criteria in a holistic scoring scale as a pedagogical tool in teaching English Language argumentative essay writing. To determine its potential, briefing sessions based on notes and checklist that contains assessment criteria derived from a holistic scoring scale used to mark essays in Malaysian secondary schools are carried out. Questionnaire is employed as the investigative tool to obtain data from selected subjects who are currently studying in Form 4 in a school in Sarawak. However, this study does not intend to make any conclusive statements about the feasibility of using assessment criteria in a holistic scoring scale as a pedagogical tool in teaching English Language argumentative essay writing. Instead, it is intended merely to look into the potential of using the aforesaid method in helping the Malaysian learners to better their performance in essay writing.